Modeling of Wind Energy Potential for Sarawak: Conceptual Design - S. M., Lawan; W. A. W. Z., Abidin; A., Baharun; T., Masri; W. Y., Chai (ENCON 2013, 2013)
Electricity is the basic need of everyone in urban and rural areas. In Sarawak, most of the rural dweller depends on diesel generator for electrical power. However, there are problems such as high cost of fossil fuel, transportation and stepping down of 33/132 kV transmission lines that pass through the areas, to overcome the aforementioned problems. Wind energy provides an alternative to the current dependency on fossil fuel. This paper presents a suitable conceptual framework of wind characteristics and energy potential modeling for rural electrification in Sarawak. The proposed concept consist of six (6) different subsystem namely; topographic, wind data collection and processing, development of numerical wind prediction model, wind speed variation and energy potentials modeling analysis, Micrositing model development and GIS model-based wind mapping.